Unleashing Agroecology in Tunisia: Highlights from NATAE's Inspiring Field Kick-Off Day - Idoudi, Zied; Tamura, Masafumi; Frija, Aymen; Kleinermann, Charles (International Center for Agricultural Research in the Dry Areas, 2024)
ICARDA, in collaboration with INAT, INGC, and local partners, hosted a participatory Field Kick-off Day to explore innovative agricultural practices for agroecology in Tunisia's semi-arid region. This initiative is part of the North African Transition to Agroecology (NATAE) project, funded by the European Commission and supported by the CGIAR Research Initiative on Agroecology and contributors to the CGIAR Trust Fund. On October 24, 2024, the El Krib Living Lab in Tunisia’s Siliana district hosted the Field Kick-off Day to mark the launch of the 2024-25 cropping season under the NATAE project. The event brought together 54 participants, including farmers, researchers, extension agents, and NGOs, with a notable 50% female participation. It introduced innovative agroecological combinations aimed at promoting sustainable farming in the region.